Mycoplasma genitalium: An Overlooked Sexually Transmitted Pathogen in Women? - Ona, Samsiya (Infect Dis Obstet Gynecol, 2016)
Mycoplasma genitalium is a facultative anaerobic organism and a recognized cause of nongonococcal urethritis in men. In women, M. genitalium has been associated with cervicitis, endometritis, pelvic inflammatory disease (PID), infertility, susceptibility to human immunodeficiency virus (HIV), and adverse birth outcomes, indicating a consistent relationship with female genital tract pathology. The global prevalence of M. genitalium among symptomatic and asymptomatic sexually active women ranges between 1 and 6.4%. M. genitalium may play a role in pathogenesis as an independent sexually transmitted pathogen or by facilitating coinfection with another pathogen. The long-term reproductive consequences of M. genitalium infection in asymptomatic individuals need to be investigated further. Though screening for this pathogen is not currently recommended, it should be considered in high-risk populations. Recent guidelines from the Centers for Disease Control regarding first-line treatment for PID do not cover M. genitalium but recommend considering treatment in patients without improvement on standard PID regimens. Prospective studies on the prevalence, pathophysiology, and long-term reproductive consequences of M. genitalium infection in the general population are needed to determine if screening protocols are necessary. New treatment regimens need to be investigated due to increasing drug resistance.